2015
DOI: 10.1186/s40174-015-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Real unit labour costs in Eurozone countries: drivers and clusters

Abstract: We examine the trajectories of the real unit labour costs (RULCs) in a selection of Eurozone economies. Strong asymmetries in the convergence process of the RULCs and its components-real wages, capital intensity, and technology-are uncovered through decomposition and cluster analyses. In the last three decades, the PIIGS (Portugal, Ireland, Italy, Greece, and Spain) succeeded in reducing their RULCs by more than their northern partners. With the exception of Ireland, however, technological progress was weak; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…There is abundant literature on testing for convergence in the EU, both at national [3,5,6] and at regional level [16][17][18][19]. Unsurprisingly, most of the literature rejects overall convergence in favour of cluster convergence.…”
Section: Economic Integration and Convergencementioning
confidence: 99%
See 2 more Smart Citations
“…There is abundant literature on testing for convergence in the EU, both at national [3,5,6] and at regional level [16][17][18][19]. Unsurprisingly, most of the literature rejects overall convergence in favour of cluster convergence.…”
Section: Economic Integration and Convergencementioning
confidence: 99%
“…). Rather, it has boosted some structural divergencies that were already present in the growth model of these economies' [5]. Similarly, Díaz del Hoyo et al [2] also find that total factor productivity is the key driver of convergence and that the differences in productivity between southern European countries and the higher-income countries existed long before the introduction of the euro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This club convergence is a possible form of conditional convergence, where economies belonging to a group of countries share similar features. Similarly, Ordóñez et al (2015) also find club convergence in competitiveness measured as real unit labour costs, and in capital accumulation and total factor productivity. According to Monfort et al (2018), the lack of real economic convergence can also be observed in income inequality and unemployment.…”
Section: Introductionmentioning
confidence: 74%
“…One consists of papers that find competitiveness to have affected growth. Ordóñez et al (2015) conclude that the economic crisis was caused by differences in competitiveness which generated real divergences and growing current account imbalances. Consistent with this view, Caporale and Gil-Alana (2014) find evidence that misalignment of the real exchange rate affects longer-term growth.…”
Section: Introductionmentioning
confidence: 97%